The complete mitochondrial genome of Huainan partridge chicken (Gallus gallus) - Shu-ying Peng; Ming-xin Lu; Min Wang; Ling Wang; Cheng-qiao Wang; Jing-ru Wang; Yun-fang Zhang; Hai-jun Zhang; Jun Li (Mitochondrial DNA. Part B. Resources, 2021)
Huainan Partridge chicken is one of the indigenous chicken breeds in China. In this study, the first complete mitochondrial DNA (mtDNA) sequence of Huainan Partridge chicken had been obtained using PCR amplification, sequencing and assembling. The mitogenome of Huainan Partridge chicken is 16785 bp in length, including a control region (D-loop), 13 protein-coding genes, 22 transfer genes and 2 ribosomal genes. The base composition of the complete mtDNA sequence is 30.27% for A, 23.73% for T, 13.50%for G, 32.50% for C. This study will provide reference for the phylogenetic analysis of Huainan Partridge chicken.